Pengaruh Critical Success Factors terhadap Keberhasilan E-Learning dalam Mendukung Pembelajaran : Systematic Literature Review - Azzam Izzudin Hasan; Alda Eva Saputri; Annisa Safa; Ftiroh Fitroh (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2022)
E-learning is considered less successful to replace normal learning methods amid the impact of the COVID-19 pandemic. The purpose of this study is to answer the question of what are the critical success factors (CSF) of the successful implementation of e-learning. This study applies the Systematic Literature Review method. Based on the results of a systematic literature review, the researcher found 162 Scopus articles in a search using Publish or Perish with Scopus Search which were then filtered into 13 selected articles for descriptive analysis. The findings show that there are 23 factors divided into five domains, namely students, instructors, design and content, systems and technology and institutions that can be considered in implementing or developing e-learning learning methods.